Distributed adaptive fault-tolerant consensus control for multi-agent systems with event-triggered communication. Issue 4 (12th March 2023) - Mu, Rui; Wei, Airong; Li, Haitao; Wang, Zi-Ming
ABSTRACT: In this paper, the distributed fault-tolerant consensus control problem is studied for multi-agent systems with event-triggered communication. Unknown time-varying actuator faults including partial loss of effectiveness and bias are taken into consideration. For the sake of fault compensations, a novel distributed event-triggered control law is put forward via the adaptive fault-tolerant technique in the leaderless network. Then, two event-triggered mechanisms are constructed, and a positive L 1 function introduced therein is greatly useful for scheduling the information transmission as well as excluding the Zeno behavior. Under the proposed protocol, the consensus errors are proved to converge to zero asymptotically in a scalable and fully distributed way. Furthermore, the results obtained in the leaderless network are extended to the leader-following case. Finally, simulation examples are conducted to confirm the validity of the presented results.